Vegetable Oil Industry in India: Key Trends and Statistics - Bansal, Anamika; Agarwal, B. K (Journal of Commerce and Trade, 2017)
Vegetable oils are extracted from plants and are composed of triglycerides, a glyceride in which the glycerol is esterified with three fatty acids. Thus, any non-animal oil obtained from the seeds or nuts of vegetable growth like corn soybeans, peanuts, cottonseeds, sunflower seeds, etc. Vegetable fats and oils are both edible and inedible. It can be flavoured by immersing aromatic food stuffs such as fresh herbs, peppers, garlic, and other spices & herbs. The vegetable oils are consumed directly, or used directly as ingredients in food - a role that they share with some animal fats, including butter and ghee. Vegetable oil is much more than a cooking oil, it is a valuable food, too. It provides us with two and half times as much energy as wheat or rice. It is understood that the industry has now taken upon itself a sustained oilseeds research and development acitivity and promote usage of non-traditional oils, soyabean, watermelon seed, Niger oils, mahua oil and rice bran oil. In this regard the effort of ‘Oliseeds Research and Development Institute’ should be commended. This has helped the farmers to procure advanced variety of seeds so as to improve the yields.